Rare complication of varicocelectomy: Suture granuloma. (28th February 2019) - Eryilmaz, Recep; Demir, Murat; Aslan, Rahmi
Abstract: After varicocelectomy, complications such as hydrocele, testicular atrophy and recurrence can be seen. Our case was a 29‐year‐old male patient who had a fistula mouth laterally on the left scrotum. In the examination and scrotal ultrasonography (USG), a foreign body was detected under the skin. The patient had a history of varicocelectomy, suggesting suture reaction. Our case is interesting because it is the first reported suture granuloma case after varicocelectomy.